Política pública de regionalização do turismo em Minas Gerais: o caso do Circuito Vale Verde e Quedas D’água - Silva, Geiziana das Dores Nunes da (2017)
This study had as a central concern the public policy of tourism regionalization in Minas Gerais, taking as reference the case of the Tourist Association of the Vale Verde and Quedas D'Água circuit. The objective of this study was to describe and analyze the contexts of the foundation and organization of the Association, to analyze its trajectory and operation in the context of the state’s public policy regionalization of tourism, in the Association between 2001 and 2016, to discuss the interactions of the Association with the public power, other institutions and society, as well as the challenges faced and results achieved in this period. For this, a qualitative analysis with exploratory approach was done in the form of descriptive and case study. The techniques used were documental analysis and interviews. The Tourist Association of the Vale Verde and Quedas D'Água circuit was created on July 19, 2001 in the municipality of Lavras. After the foundation there was a period of inactivity without documentary records, later in 2005 there was the return and records of the activities. It was observed that the highest gains and activities that had the greatest intensity are related to the periods in which there was a state management with orientation of more technical activities, with greater financial investment for the sector. The research identified that the fact that the State creates a public policy and doesn’t give technical support, doesn’t guarantee the feasibility or success of it. Finally, as to the need for tourism policy to be decentralized and regionalized, it was understood that in the context of the circuits, in the case studied, with all practical difficulties, there were nevertheless occasional contributions over the 15 years of the association's existence.